MOUNTAIN GLACIERS OF THE PLEISTOCENE LAST GLACIAL MAXIMUM IN THE NORTHWESTERN BARGUZIN RANGE (NORTHERN LAKE BAIKAL): PALEOGLACIAL RECONSTRUCTION - Osipov E.Yu.; Grachev M.A.; Mats V.D.; Khlystov O.M.; Breitenbach S. (My University, 2003)
Outlines and parameters of glaciers formed during the Pleistocene Last Glacial maximum (MIS 2) have been reconstructed based on remote sensing and field investigation of the glaciology and geomorphology of a 3293 km2 key site in the Barguzin Range. The studies included (i) deciphering aerial photographs and satellite imagery, (ii) detection of glacier traces along 100 km of the Baikal shoreline and on divides, and (iii) data processing using GIS tools. The results indicate discontinuous mesh-type glaciation with local ice caps on mountain divides and dendritic valley glaciers. The largest lobes were 60-70 km long and spread outside their valleys into the North Baikal basin. Almost a half of the study area (∼46 %, 1528 km2) was covered with ∼ 174 km3 of ice. The maximum ice thickness attained 800 m in ponded depressions. Glaciology, lithology, and seismic stratigraphy indicate that for the Last Glacial (MIS 2-4), glaciers delivered about 30.6×1012 kg of terrigenous load into the lake from the Tompuda, Shiril'dy, and Frolikha drainage basins, and the mean annual rate of glacial erosion was about 0.16 mm.
Keywords: Late Pleistocene; glaciation; Last Glacial maximum; paleoglacial reconstruction; GIS; glacial erosion; Lake Baikal; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен